Brandlink Business-to-Business E-commerce web Solution - Janjua, Ali Nasir Muhammad; Arif, Muhammad (My University, 2014)
Today, business is moving rapidly towards web technologies due to their portability, efficiency and multi-platform compatibility. Web technologies are impacting the way of businesses and their management. It is very difficult to manage many business relationships manually or even using some desktop application because there are multiple and distributed users. Using web based systems it’s easy to manage distant users and speed-up business transactions. This project has produced a web based system which aims to make the business transactions speedy, easy to execute, and reliable. This report presents the importance of web based systems in modern world and provides the mechanism that how business-to-business e-commerce solutions work. Specifically the report discusses the Brandlink Business to Business e-commerce solution which is kind of a complete management system facilitating manufacturers/brands and sellers/retailers to do business transactions between them through a web based e-commerce system. It also addresses the important development phases, resulting outcomes, and technical description of different sections of the Brandlink B2B solution (supplier/brand, store/retailer, and admin). A formalized specification of the requirements is developed keeping the documentation simple and clear. Testing of solution is performed at the component level and bugs appeared during testing are listed in this report. The end product is a complete web based B2B ecommerce system able to be deployed in real environment. The solution reduces the transaction processing time & cost, improves efficiency, and provides reliability compared to manual business transactions.
Keywords: Data- och informationsvetenskap; Computer and Information Science